Gulf countries trade relations with the United States - Н.К., Байбусинова (Journal of Oriental Studies, 2020)
The article examines the complex structure of trade and economic relations between the Gulf States and the United States, complicated by military conflicts and affected by the influence of superpowers. The main purpose of this article is to reveal the history of the Gulf countries trade relations with the United States. The research methods included comparison and historical analysis of the facts of the Persian Gulf countries development. In the modern world, in view of the increasing role of the globalization process, the importance of economic integration organizations is growing. In this regard, an important position in the structure of economic groups is the Council for Cooperation of the Arab States of the Persian Gulf. The close relations of the Arabian monarchies with the United States have largely determined their own development paths and today form the basis of their economic policy. The situation in the development of trade relations between the Gulf States is also conditioned by the US intervention and recent events in Iran, which may again lead to an escalation of the military conflict and stagnation of trade relations. In view of this, it is necessary to use a political dialogue that does not allow for war, which can result in a decrease in trade indicators in the region. As a result of the research, it was possible to determine the main aspects of cooperation between the Gulf States and the United States, in terms of emerging problems and the complexity of mutual historical development. Key words: the Persian Gulf, the United States, trade relations, integration, the Arab six, military conflict, oil.